A new species of Polygonatum Mill. (Asparagaceae) from Guizhou, China (Bangladesh Journal of Plant Taxonomy, 2016)
A new species Polygonatum sinopubescens from Yinjiang County, Guizhou Province, South-west China is described and illustrated. This species was found growing in evergreen broad-leaved forests or mixed needle-leaved and evergreen broad-leaved forests on slopes at altitudes of 870-930 m. It is related to Polygonatum filipes Merr. ex C. Jeffrey & Mc Ewan, but differs from the latter by pubescent stems, petiole, peduncle and pedicel, leaf blade shortly dense pubescent on abaxial surface, 2-3-flowered inflorescences and filaments 7-11 mm long.Bangladesh J. Plant Taxon. 23(1): 7-11, 2016 (June)